Italians in Ingham and Innisfail in World War II: Selective and Not Mass Internment? - Martinuzzi O'Brien, Ilma (Spunti e Ricerche, 2016)
During World War II, a quarter of all the Italians interned in Australia came from the two towns of Ingham and Innisfail in North Queensland. About half of all internments of Italian-born persons in Australia came from Queensland. Although the Italian-born populations of Victoria and Queensland were approximately the same size, Queensland interned roughly 15 times as many people of Italian origin as did Victoria. In this article I will consider some of the factors behind these disproportionate internments in Queensland and explore their impacts on the communities involved.